Intracrine androgen biosynthesis, metabolism and action revisited - Schiffer, Lina; Arlt, Wiebke; Storbeck, Karl-Heinz (Molecular and cellular endocrinology, 2018)
Androgens play an important role in metabolic homeostasis and reproductive health in both men and women. Androgen signalling is dependent on androgen receptor activation, mostly by testosterone and 5α-dihydrotestosterone. However, the intracellular or intracrine activation of C19 androgen precursors to active androgens in peripheral target tissues of androgen action is of equal importance. Intracrine androgen synthesis is often not reflected by circulating androgens but rather by androgen metabolites and conjugates. In this review we provide an overview of human C19 steroid biosynthesis including the production of 11-oxygenated androgens, their transport in circulation and uptake into peripheral tissues. We conceptualise the mechanisms of intracrinology and review the intracrine pathways of activation and inactivation in selected human tissues. The contribution of liver and kidney as organs driving androgen inactivation and renal excretion are also highlighted. Finally, the importance of quantifying androgen metabolites and conjugates to assess intracrine androgen production is discussed. •Serum concentrations of active androgens do not account for all androgen activity.•Dysregulation of intracrine androgen pathways is relevant to numerous disease states.•Androgen metabolites and conjugates can be of diagnostic value.•11-oxygenated C19 steroids contribute to the androgen pool.•11βHSD enzymes are important modulators of both glucocorticoid and androgen activity.